SAVI Approach to Students' Creative Thinking Abilities in Class VI Elementary School Science Content - Ni Putu Sillvia Sari Dewi; Putu Nanci Riastini (Universitas Pendidikan Ganesha, 2023)
Lack of diverse approaches and low students' creative thinking abilities during the science learning process. To overcome these problems, an innovative approach is needed to develop students' creative thinking abilities. This research examines differences in students' creative thinking abilities in science content between the SAVI approach and conventional learning in class VI elementary school. This includes quasi-experimental research (Quasi-Experimental) with a non-equivalent post-test-only Only Control Group Design. The population of this study was 110 grade VI elementary school students. The sample in this research was carried out by random sampling. The models obtained were 25 class VI SD 2 students as the experimental group and 24 class VI SD 5 students as the control group. Data collection in this research used the test method with descriptive test instruments. The data analysis used is descriptive and inferential statistical analyses (t-test). Based on the analysis results, it was found that the SAVI approach had more influence on students' creative thinking abilities. The SAVI approach could improve students' creative thinking abilities. This research implies that applying the SAVI approach can increase student activity, solve problems, and develop students' creative thinking abilities.